2022
DOI: 10.3389/fimmu.2022.947568
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of STAT3 in NK-Cell Tumor Surveillance

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a member of the Janus kinase (JAK)-STAT pathway, which is one of the key pathways contributing to cancer. STAT3 regulates transcription downstream of many cytokines including interleukin (IL)-6 and IL-10. In cancer, STAT3 is mainly described as a tumor promoter driving tumor cell proliferation, resistance to apoptosis, angiogenesis and metastasis and aberrant activation of STAT3 is associated with poor prognosis. STAT3 is also an important driver of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 171 publications
(246 reference statements)
0
11
0
Order By: Relevance
“…STAT3 underlies many complex mechanisms of both tumorigenesis and NK cell immune function; our findings demonstrate it may also be a suitable target for prevention of NK memory priming as a third pathogenic aspect to CAEBV. 23 Our results highlight that it is crucial to initiate early treatment of CAEBV with HSCT or cytokine inhibitors, before EBV infected NK cells establish a memory population, and suggest that further investigation into the effects of memory-priming cytokines and STAT3 inhibitors may present new therapeutic opportunities.…”
Section: Clinical Trial Registration Information (If Any)mentioning
confidence: 74%
“…STAT3 underlies many complex mechanisms of both tumorigenesis and NK cell immune function; our findings demonstrate it may also be a suitable target for prevention of NK memory priming as a third pathogenic aspect to CAEBV. 23 Our results highlight that it is crucial to initiate early treatment of CAEBV with HSCT or cytokine inhibitors, before EBV infected NK cells establish a memory population, and suggest that further investigation into the effects of memory-priming cytokines and STAT3 inhibitors may present new therapeutic opportunities.…”
Section: Clinical Trial Registration Information (If Any)mentioning
confidence: 74%
“…The STAT3 protein, belonging to the STAT family, serves as a versatile transcription factor implicated in numerous physiological processes, such as cellular proliferation and programmed cell death. [16][17][18] In their study, Macchi et al discovered that leptin induced an up-regulation of STAT3 phosphorylation in HepG2 cells. [19] Additionally, previous observations have indicated that leptin facilitates the progression of OA through the activation of the STAT3 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…We next examined the potential signaling pathways that might mediate the effects of tumor stromal cells on CSCs. According to the findings in recent studies, there are several signaling pathways, including JAK/STAT [ 59 , 60 , 61 , 62 , 63 ], PI3K/Akt [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], NF-kB [ 71 , 72 , 73 , 74 , 75 , 76 ], and TGF-β signaling [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ], that could possibly be mediating the stromal cell functioning in PTC, as these signaling pathways have been found to be involved in the effects of stromal cells on tumor cells [ 59 , 60 , 61 , 62 , 63 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. To unveil the potentially engaged signaling pathways, we examined the expression of specific molecules that indicate different signaling pathway activities with Western blotting analyses.…”
Section: Resultsmentioning
confidence: 99%